Soil Responses on Peatland Fire: Case Studies in Jambi and Central Kalimantan - Lailan Syaufina; Bambang Hero Saharjo; Ati Dwi Nurhayati; Erianto Indra Putra; Wardana Wardana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Jambi and Central Kalimantan Provinces are among fire-prone provinces that experience fire annually. The provinces have large peatland areas, which are susceptible to fire. The peatland fire cause impacts on peat soil characteristics, including peat physical and chemical properties. The study was conducted in Sinar Wajo Village, Jambi and Kalampangan and Tumbang Nusa villages, Central Kalimantan Provinces. Land clearing activities for agriculture farming mostly caused forest and land fire in both locations. This study compares physical and chemical soil characteristics on burned and unburned peatland areas in Jambi and Central Kalimantan. Samples of peat soil were taken from 0-20 cm depth. Peat soil chemical and physical properties obtained from laboratory analyses were statistically analyzed to compare the properties in burned and unburned areas using JASP. The study resulted in significant differences for Potassium, Sodium, and Calcium, which indicate higher content in the burned plots than the unburned plots. Key words: Chemical soil properties, land clearing, peatland, physical soil properties